الهجرة النّبوية - دراسة في الأسباب والمنجزات - مراد, لكحل (Université de M'sila, 2020)
من أبرز أحداث السيرة النبوية ووقائعها هجرة الرسول صلى الله عليه وسلم وأصحابه من مكة إلى المدينة، فبفضلها كتب لرسالة الإسلام القبول في الأرض والتمكين بعدها، وعلى هذا الأساس جاءت دراستنا هذه من أجل معالجة الإشكالية التالية : ما هي أهم الأسباب والدّوافع التي بعثت على هجرة الرسول صلى الله عليه وسلم وأصحابه؟ وماهي أهم نتائج هذه الهجرة المباركة ومنجزاتها؟ وفي خضم ذلك عالجنا الإشكاليات الفرعية الآتية: ماهي الوسائل والطرائق التي استخدمها زعماء مكة لمحاربة الدّعوة والقضاء عليها؟ وإلى أي مدى أثرت هذه الطرائق في الحد من توسيع نطاق الدّعوة؟ وكيف سعى رسول الله إلى إرساء قواعد دولة جديدة بيثرب؟ وبعد معالجة هذه الإشكاليات يتضح جليا أن الظروف التي أحاطت بالدعوة في بداية أمرها عسّرت عملية نشرها وبثّها في مكّة وما جاورها، إذ استخدمت قريش كلّ وسيلة في سبيل القضاء على الدّعوة الإسلامية، من صدّ وإغراء، وتعذيب للمؤمنين، وتشويه للرسالة وصاحبها، مما جعل الهجرة إلى يثرب أمرا لازما تقتضيه مصلحة الدّعوة، وقد سعى رسول الله بعدها لتثبيت دعائم الدّولة الجديدة فكانت أولى إنجازاته بناء المسجد والمؤاخاة بين المهاجرين والأنصار، وإصدار الوثيقة أو الدّستور الاسلامي في المدينة، وإعداد جيش لحماية الدّولة، والسّعي لتحقيق الأهداف العالمية لرسالة الإسلام. Abstract: Among the most prominent events of the Prophet’s life, the emigration of the Messenger and his companions from Mecca to Medina, on this basis, our study came to answer the following questions: What are the most important reasons and motives that led to the emigration of the Messenger and his companions? What are the most important results and achievements of this blessed migration? After searching, it is clear that the circumstances that surrounded the islamic call at the beginning made it difficult to publish and broadcast it in Makkah and its environs, as Quraish used all means in order to eliminate the Islamic call, such as repelling, tempting, torturing the belieavers, and distorting the message and the messenger, which made the immigration to Yathrib a necessity for the benefits of the call, after that the Messenger of God sought to install the pillars of the new state so he founded the mosque, united the immigrants and the Ansar , issued the contitution of the Medina and built an army. After that, he sought to spread the islamic call throughout the world.
Keywords: كلمات مفتاحية: الهجرة، مكة، المدينة، أسباب، منجزات. ; Keywords: immigration, Mecca, Medina, causes, achievements